ASSESSING THE LEVEL OF KNOWLEDGE AND ATTITUDES ABOUT ORAL HEALTH BEHAVIORS OF PRESCHOOLERS - Catalina Iulia Saveanu; Daniela Anistoroaei; Loredana Golovcencu; Alexandra Ecaterina Săveanu (Romanian Dental Association for Education, 2019)
Assessing the level of knowledge and attitudes about sanogenic behaviors of preschoolers is a predictive factor in assessing the level of knowledge and orientation of health education lessons. Aim:The purpose of the study was to analyze the level of knowledge and attitudes among preschoolers in Iasi before and after applying educational messages. Material and method: The group included 82 preschoolers, to whom 22 questions were applied using the questionnaire method before and after the health education lessons. Data processing was performed with SPSS14Windows with p <0.05%. Results and discussion: Subjects with an average age of 4.38 years (± 0.826) have multiple knowledge, and after applying audio-visual information methods, the final percentages of the analysis have increased the results being statistically significant p≤0.05. Conclusions: Within the limits of this study, we can conclude that oral health education is an easy way to approach and with remarkable results.